Increased Risk of Systemic Lupus Erythematosus in Patients With Helicobacter pylori Infection: A Nationwide Population-Based Cohort Study - Wu, Meng-Che; Leong, Pui-Ying; Chiou, Jeng-Yuan; Chen, Huang-Hsi; Huang, Jing-Yang; Wei, James Cheng-Chung (Frontiers in Medicine, 2020)
Helicobacter pylori (HP) infection is associated with systemic lupus erythematosus (SLE), but the related results have been controversial. Therefore, this study investigated the association between HP infection and SLE by using a nationwide longitudinal population-based cohort. We identified 41,651 patients with HP infection and 83,302 matched controls between 2000 and 2013 from the Longitudinal Health Insurance Research Database of the National Taiwan Insurance Research Database. Age, gender, comorbidities, and medical visits were matched at a 1:2 ratio by using propensity score analysis. The adjusted hazard ratio (aHR) of SLE was calculated by multiple Cox regression. Furthermore, sensitivity test and stratified analysis were performed. The SLE incidence rate was 1.17 (95% confidence interval [CI]: 0.89–1.54) per 100,000 person months in the HP cohort, and the hazard ratio was 1.63 (95% CI: 1.12–2.37) in comparison with the propensity score-matched control cohort. After multivariate adjustment, patients with HP infection had a significantly high overall aHR (1.58; 95% CI: 1.08–2.30) of SLE. Stratified analysis revealed that the aHR of 8.23 (95% CI: 1.77–38.32) in patients <30 years old, and the p for interaction between age and HP infection was 0.039. For age–sex subgroup analysis, the highest aHR of 12.74 (95% CI: 1.55–104.59) in young (aged <30 years) female patients with HP infection. HP infection is associated with a 1.63-fold increased SLE risk, particularly with female patients aged <30 years. Future research is required to elucidate the underlying mechanism of this association.